2017
DOI: 10.1021/acs.jpcc.7b02344
|View full text |Cite
|
Sign up to set email alerts
|

General Acid-Type Catalysis in the Dehydrative Aromatization of Furans to Aromatics in H-[Al]-BEA, H-[Fe]-BEA, H-[Ga]-BEA, and H-[B]-BEA Zeolites

Abstract: Al, Ga, Fe, and B metal substituents have been examined for their ability to change the Brønsted acid strength of BEA zeolite and inhibit undesired hydrolysis in the production of aromatics from furan, 2-methylfuran, and 2,5-dimethylfuran. We employed electronic structure calculations to examine this series of furans in H-[Al]-, H-[Fe]-, H-[Ga]-, and H-[B]-BEA zeolites. These calculations were used to parametrize a microkinetic model to make direct comparisons to experiments run with furan and DMF in the weake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 59 publications
(150 reference statements)
2
29
0
Order By: Relevance
“…Since the addition reaction is bimolecular, the transition state C_TS 9 with a roof-shaped spatial geometry is formed during the addition process. A double bond forms, so active-H cannot participate in the reaction, but active H affects the electronic structure around the reactant and can also reduce the energy required for the reaction to a certain extent, which is consistent with the report by Patet et al Patet et al 2017 . The third step is that active-H promotes the breaking of the ether bond and the free water molecules in the reaction process, and the oxygen on the ring form a hydrogen bond, preparing for the water addition reaction in the fourth step.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Since the addition reaction is bimolecular, the transition state C_TS 9 with a roof-shaped spatial geometry is formed during the addition process. A double bond forms, so active-H cannot participate in the reaction, but active H affects the electronic structure around the reactant and can also reduce the energy required for the reaction to a certain extent, which is consistent with the report by Patet et al Patet et al 2017 . The third step is that active-H promotes the breaking of the ether bond and the free water molecules in the reaction process, and the oxygen on the ring form a hydrogen bond, preparing for the water addition reaction in the fourth step.…”
Section: Resultssupporting
confidence: 90%
“…To study the Diels-Alder cycloaddition reaction of furan and ethylene on the Brønsted-acidic molecular sieve, Patet et al used electronic structure calculations and microscopic kinetic models, and the subsequent dehydration reaction of furan and ethylene Patet et al 2017 . The electronic structure calculation showed that the acid strength of the Brønsted-acidic zeolite changes with the changes of Al, Ga, Fe, and B metal substituents.…”
Section: Wangmentioning
confidence: 99%
“…[43] Reaction system Reactions were carried out in a0.5 Lstirred batch autoclave reactor (Autoclave Engineers EZE seal) with ab ackpressure regulator and a PID temperature controller.I natypical experiment, 0.175 Lo fa n aqueous solution of d-(À)-glucose (5.83 g) and b-zeolite (0.466 g) were used. 99.5 %) and sodium hydrogen carbonate (!…”
Section: Methodsmentioning
confidence: 99%
“…19,20 While this assumption holds true for bridging hydroxyls in aluminosilicates, 29 challenges associated with extending it to weak acids have been previously illustrated on [B]-substituted zeolites. 30,31 Gorte and co-workers have shown that in the course of a TPD, isopropylamine can desorb without reacting on the weakly Brønsted acidic centers of [B]-substituted MFI, leading to the undercounting of available BAS. 31 On weaker BAS where the barrier to molecular desorption is reduced, the assumption of negligible rates of molecular desorption may not hold true.…”
Section: Brønsted Acidicmentioning
confidence: 99%